Evaluation of dentinal surface with clinical microscope after intra-radicular - Rielson José Alves Cardoso; Mary Caroline Skelton Macedo; Rosa Maria Freire; Moacyr Benassi (Faculdade São Leopoldo Mandic, 2008)
Objective: To evaluate the time spent and possible fissure lines, fractures and other damage caused on the dentinal surface around theintra-radicular retainer submitted to ultrasonic vibration to remove it, using a clinical microscope. Methods: The roots of 15 bovine mandibular central incisors were used. These contained Flexi-Post No. 3 intra-radicular retainers cemented with RelyX CRA® resinous cement and were included in an artificial alveolus, surrounded by a layer of silicone. The retainers were submitted to ultrasonic vibration with the ENAC model EO-5 appliance at maximum power, and after removal, an evaluation was made by the naked eye, and another with a clinical microscope, at magnifications of 5, 8, 12.5 and 20 times. Results: The results showed that no dentinal surface presented fissure lines, cracks or other damage, and that the mean time for removalof the retainers was 13.25 minutes. Conclusion: Ultrasound was shown to be an efficient and safe appliance for intra-radicular retainer removal.